Die Fabry-Kardiomyopathie als Differenzialdiagnose des akuten Koronarsyndroms - Oder, Daniel; Störk, Stefan; Wanner, Christoph; Ertl, Georg; Weidemann, Frank; Nordbeck, Peter (DMW - Deutsche Medizinische Wochenschrift, 2017)
The progressive cardiomyopathy in patients with Fabry disease is often accompanied by angina pectoris and elevated levels of high-sensitive troponin T (hs-TnT), potentially mimicking acute coronary syndrome. Here, we present to representative cases with focus on clinical, diagnostic and therapeutic settings. An overview on the cardiomyopathy associated with Fabry disease and its role as differential diagnosis of acute coronary syndrome is provided. Fabry cardiomyopathy might exhibit similar clinical and biochemical constellations as seen in acute coronary syndrome. Thus, Fabry cardiomyopathy should be considered a differential diagnosis in acute coronary syndrome, particularly in patients demonstrating left ventricular hypertrophy of unknown origin.
Keywords: Akutes Koronarsyndrom; Fabry Kardiomyopathie; Troponin; Hypertrophe Kardiomyopathie; Lysosomale Speicherkrankheit; Myokardinfarkt